THE INFLUENCE LEARNING MODEL GUIDED INQUIRY AND CREATIVITY ON HIGHER COGNITIVE - Sari Wahyuni Rozi Nasution; Nurdin Bukit; Eva M. Ginting (Jurnal Pendidikan Fisika, 2016)
The purpose of this research was to know the different between the using of guided inquiry and direct instruction learning models on creativity and students’ physic high cognitive learning result. This research was quasy experimental research by applying two group pretest-postes design with physic high cognitive test and creativity questionairres as the instruments. Data in this research was analyzed by using two ways anova. The results showed that Guided Inquiry learning model is better in improving the cognitive achievement of high student. The research data was taken from the student who is attending a physics lesson from one of the private schools in North Sumatra numbered 68 students. Test hypothesis testing using General Linear Model (GLM) univariate at significance level α = 0.05.